Efek Protektif Methylprednisolone pada Testis Kontralateral Tikus Wistar yang dilakukan Torsio-Detorsio: Ditinjau dari variabel pemeriksaan Histopatologi Johnsen score, jumlah lapis sel tubulus seminiferus, jumlah sel nekrosis, dan derajat adhesi neutrofil - Wibisono, Dimas Sindhu; Nugroho, Leonardo Cahyo; Muhammad, Krisna; Fauzi, Ardi; Putra, Adityas Mahendra; Hidayat, Afif Iman (RSUP Dr. Kariadi, 2021)
Background: Testicular torsion is an emergency situation and requires immediate surgery. Testicular torsion accounts for 13-54% of cases of acute pediatric scrotal disease and occurs in 1 in 4,000 men aged <25 years and 1 in 160 men over 25 years. Even though the intervention was carried out for less than 6 hours, post-detortion testicular tissue mortality was still high, due to reperfusion ischemic injury due to excessive production of ROS (Reactive Oxygen Species). The contralateral testis is often affected after torsion-detortion due to the effects of ROS. The provision of additional therapy after detortion is an urgent need to be found because it can reduce the death of testicular tissue due to reperfusion ischemic injury. Methods: It is an experimental study with a randomized controlled study design with post test only control group design. The research sample was 18 Wistar rats divided into 3 groups. Torsion of the ipsilateral testis is performed, then detortion and intravenous therapy are administered. The apoptotic index (infertility) was observed on the Johnsen score variable, the number of seminiferous tubular cell layers, neutrophil adhesion and the number of necrotic cells in the Eosin Hematoxyline in the contralateral testis. Furthermore, statistical analysis is carried out, the results are presented in tables and figures. Results: There was a significant difference between the Methylprednisolone group and the Torsion Detortion group with p = 0.008 in the Johnsen score variable and the number of seminiferous tubular cell layers. Discussion: Methylprednisolone as an anti-inflammatory has been proven in its function to reduce ROS so that it can reduce reperfusion ischemic injuries.